Managing double and multiple crises : examining crisis dynamics, organizational responses, and stakeholder activism - Damayanti, Ratna (2017)
The black swan of crises – a double or multiple crisis event – may well cripple any organization despite it being crisis-ready. Using a multiple-case study method comprising six individual case studies of organizations and industries that had the misfortune of experiencing a second crisis before the first one is resolved, this study offers: A novel conceptualization of the double / multiple crisis; variations of the double / multiple crisis; and strategies rooted in Coombs’ (2012) Situational Crisis Communication Theory. This study found that for double and multiple crises, the original crisis does not affect organizational reputation the way crisis history does: Biernat’s (2012) assimilation-contrast theory may better explain how stakeholders attribute blame to companies experiencing the second crisis in a double crisis, or companies experiencing the latter crises in a multiple crisis situation. A contrast effect occurs when a double crisis situation comprises of two crises falling under different crisis clusters; in such instances, this study builds on SCCT recommendations to explore new frontiers of crisis management and communication response. This study extends Coombs’ Situational Crisis Communication Theory (2012) to account for a new variable: The double or multiple crisis. This study also offers the decision making framework for double crisis, to help practitioners choose appropriate SCCT strategies in a real-life double crisis, and the amount of resources to allocate to manage the crisis. Keywords: double crisis, multiple crisis, crisis history, crisis communication strategies